Kajian Dugaan Pelanggaran Etik Anggota DPR yang Terbukti Melakukan Pidana Pemilu - La Ode Risman (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The existence of the Council's Honorary Court as a supporting tool is contained in Article 119 of Law Number 17 of 2014 concerning MD3 in conjunction with Law Number 2 of 2018 concerning MD3 in conjunction with Law Number. 13 of 2019 concerning MD3. That the Council's Honorary Court was established by the DPR with the aim of maintaining and upholding the honor and dignity of the DPR as a representative institution of the people. That the implementation of the Election which is carried out directly is a manifestation of the implementation of democracy which is a manifestation of the sovereignty of the people. In the election, violations of the law were found as regulated in Law Number 7 of 2017 concerning Elections. That election crimes are a form of violation of the law related to acts of falsification of documents, money politics and there is also intimidation of voters and others. That these actions are alleged violations of election crimes because they are contrary to laws and regulations. That to ensure the existence of an election crime, it must go through a court process with a judge's decision, which must first be processed by the Gakkumdu Center, which is an element of Bawaslu, the National Police, and the Attorney General's Office of the Republic of Indonesia. That if proven to have committed an election crime as stated in the district court decision, the legislative candidate has committed an ethical violation, although this must be processed legally in accordance with the mechanism regulated in the DPR Council's Ethics Court, namely referring to the MD3 Law, Regulation of the People's Representative Council Number. 1 of 2015 concerning the Code of Ethics of the People's Representative Council of the Republic of Indonesia and Regulation of the People's Representative Council Number. 2 of 2014 concerning the Procedures of the Council's Ethics Court.